Dinamika Pemekaran Wilayah Dan Implikasinya Terhadap Pemerintahan Daerah Di Lampung Selatan - Abdul Halim; Dita Permata Sari; Kalyya Maharani; Mona Safitri; Ni Luh Lola Mika Fatmawati (Penerbit Hellow Pustaka, 2025)
Territorial expansion (pemekaran wilayah) is a form of decentralization within the framework of regional autonomy aimed at improving the efficiency of public services, accelerating development, and shortening the span of government control. This article aims to analyze the dynamics of territorial expansion in South Lampung Regency and its implications for regional governance. The method used is a qualitative approach involving literature studies, documentation, and in-depth interviews with several key informants. The findings indicate that territorial expansion in South Lampung, such as the establishment of Pesawaran and Pringsewu Regencies, has had a significant impact administratively, in terms of public service delivery, as well as on local socio-political dynamics. However, challenges such as elite interest conflicts, development disparities, and institutional capacity constraints remain obstacles to achieving effective and efficient governance. Therefore, continuous evaluation of expansion policies and the strengthening of regional government capacity are necessary.